Results of EAHP's 2019 Medicines Shortages Survey - Miljković, Nenad; Batista, Aida; Polidori, Piera; Kohl, Stephanie; Horák, Petr (European journal of hospital pharmacy, 2020)
AIMS AND OBJECTIVES: The aim of the 2019 EAHP Medicines Shortages Survey was to collect information on reasons and management strategies for medicines shortages as well as details on their impact on patients. The survey targeted hospital pharmacists (HPs), physicians (PHYs), nurses (NRS) and other healthcare professionals (OHCPs). A separate set of questions addressed patients (PTNs). METHODS: A 28-question survey was conducted by EAHP, collecting information from European HPs, PTNs, NRS, PHYs and OHCPs on the shortage situation in their respective countries. The survey ran from 7 November 2019 to 13 January 2020. The results were analysed by EAHP. RESULTS: There were 2136 HP responses to the 2019 survey compared with 1666 in 2018. While 95% of HPs and 89% of OHCPs consider medicine shortages a current problem, only 71% of PHYs and 62% of NRS state the same. Shortages of active pharmaceutical ingredients (72%), manufacturing (72%) and supply chain problems (49%) are leading causes of shortages according to HPs, while PHYs (40%) and NRS (37%) consider the pricing to be their driver. Antimicrobials and oncology medicines were most affected by shortages in 2019. Compared to 2018, the percentage of respondents who reported shortages of oncology medicines increased from 39% to 47% in 2019. HPs (42%), PHYs (36%) and OHCPs (38%) consider delays in care as the main consequence of medication shortages. The satisfaction with reporting systems for medicine shortages decreased from 56% in 2018 to 48% in 2019 for HPs, while they remain low for PHYs (36%). CONCLUSIONS: Medicines shortages affect patient care and healthcare professionals' everyday tasks. Better enforcing of the mandatory early notification of shortages and structured mitigation response is recognised by all respondents as best strategy to tackle shortages.
Keywords: Humans; farmaceuti; lidé; Patient Care; Evropa; Pharmacy Service, Hospital; nemocniční lékárny; průzkumy a dotazníky; Drug Costs; Surveys and Questionnaires; náklady na léky; péče o pacienta; Health Personnel; Drug Industry; léčivé přípravky; farmaceutický průmysl; Europe; zdravotnický personál; Pharmaceutical Preparations; Pharmacists